(untitled) (Journal of Legal Studies, 2015)
The role of customs has changed significantly over the past 50 years to adapt to the evolution of international trade. Before containerisation, goods were carried in bulk, boxes or nets in a ship hold. It took several days to unload the cargo one piece at the time, giving customs authorities time to clear the goods and collect duties. When the first containership "Gateway City‟ made its maiden voyage in 1957 from Port Newark to Miami it allowed dockworkers to unload cargo at a rate of 264 tons an hour. In the 80‟s, when the current Community Customs Code was conceived, a crane at a port could unload 1,000 tons per hours. Today, a single crane can handle 3,500 tons per hour, unloading a 12000 TEU containership in just a half day. This advance in productivity is putting pressure on border agencies to process shipments much faster in order to avoid creating a bottleneck at the borders.